Evidence for the persistence of monoclonal expansions of CD8+ T cells following primary simian immunodeficiency virus infection. - Wilson, J; Cranage, M; Cook, N; Leech, S; Mcmichael, A; Callan, M (1998)
A longitudinal study of the CD8+ TCR variable (Vbeta) chain repertoire was performed in rhesus macaques experimentally infected with simian immunodeficiency virus (SIV) using both TCR Vbeta chain-specific monoclonal antibodies and TCR beta chain CDR3 length analysis. Expansions of subpopulations of CD8+ T cells were detected during the acute phase of SIV infection. In all monkeys studied, monoclonal expansions persisted for at least 18 months and increasingly dominated the repertoire of CD8+ T cells expressing the relevant Vbeta chain. This study shows that persistent CD8+ T cell expansions develop in response to a virus infection. This is important not only for our understanding of the T cell response to viruses but also for understanding the factors that determine the normal CD8+ TCR repertoire.